Quantum superposition of thermodynamic evolutions with opposing time’s arrows - Giulia Rubino (Nature Portfolio, 2021)
When watching a movie of a physical process, one can conjecture whether it is running forward or backward in time by examining key physical parameters in the process. Here, the authors show that superpositions of (thermodynamic) quantum processes with opposite time’s arrows are also physically possible and observable, and explore the thermodynamic role played by the interference term.